Transcriptome profile analysis reveals the regulation mechanism of floral sex differentiation in Jatropha curcas L. Issue 1 (December 2017) - Hui, Wenkai; Yang, Yuantong; Wu, Guojiang; Peng, Changcao; Chen, Xiaoyang; Zayed, Mohamed
Abstract The seeds ofJatropha curcas contain a high percentage of biodiesel. However, low seed yield which was limited by its poor female flowers was a bottleneck for its utilization. Here, we compared the transcriptomic profiles of five different samples during floral sex differentiation stages using Illumina Hiseq 4000. Our results showed that hundreds of differentially expressed genes (DEGs) were detected in floral sex initiation period, but thousands of DEGs were involved in the stamens and ovules development process. Moreover, the DEGs were mainly shown up-regulation in male floral initiation, but mainly down-regulation in female floral initiation. Male floral initiation was associated with the flavonoid biosynthesis pathway while female floral initiation was related to the phytohormone signal transduction pathway. Cytokinin (CTK) signaling triggered the initiation of female floral primordium, thereafter other phytohormones co-promoted the female floral development. In addition, the floral organ identity genes played important roles in floral sex differentiation process and displayed a general conservation of the ABCDE model inJ. curcas . To the best of our knowledge, this data is the first comprehensive analysis of the underlying regulatory mechanism and the related genes during floral sex differentiation inJ. curcas, which help in engineering high-yielding varieties ofJ. curcas .